Functional and Aesthetic Qualities of The Visual Arts in Public Spaces - Okeke, Josiah (Journal of Language Literature and Arts, 2025)
One of the inherent attributes of the Visual Arts lies profoundly in the realm of aesthetics, which defines its uniqueness. Nevertheless, it is not devoid of functional qualities; rather, it combines both beauty and utility, making it a discipline with remarkable potential. The field of Visual Arts thus encompasses both functional and aesthetic characteristics, contributing significantly to the visual appeal of public spaces. However, despite these dual qualities, it is unfortunate that few scholars have thoroughly examined their core values in public spaces. This paper specifically aims to critically explore the functional and aesthetic dimensions of the Visual Arts within such spaces. To achieve this, it is first necessary to provide an overview of the role of Visual Arts in society, which serves as the foundation of this study. In conclusion, this research seeks to enhance the appreciation of art in public spaces. It is therefore recommended that governments and communities commission artists to create works that enrich public spaces while considering their emotional and therapeutic significance. Additionally, artists should be encouraged to produce more monumental works as commemorative structures and as a means of enhancing the aesthetic experience of public environments.